AB0431 The Effect of Tocilizumab on Bone Mineral Density in Patients with Methotrexate-Resistant Active Rheumatoid Arthritis. (10th June 2014) - Kume, K.; Amano, K.; Yamada, S.; Kanazawa, T.; Ohta, H.; Hatta, K.; Amano, K.; Kuwaba, N.
Abstract : Background: Rheumatoid arthritis (RA) is associated with systemic bone loss.[1-3] Rheumatologists should have strategies to prevent bone loss in RA patients.[4] Interleukin-6 (IL-6) is a major cytokine involved in the pathology of RA, and may also promote osteoporosis.[5, 6] Tocilizumab (TCZ) is an IL-6 receptor inhibitor, which is highly effective in the treatment of RA.[7, 8] Several reports have suggested that tumor necrosis factor (TNF) inhibitors prevent bone loss;[9, 10] however, there is no evidence that TCZ affects bone mineral density (BMD). Objectives: To analyze the effects of therapy with tocilizumab (TCZ), an anti-interleukin-6 receptor antibody on the bone mineral density (BMD) of the lumbar spine and femoral neck in patients with rheumatoid arthritis (RA). Methods: Eighty-six patients with active RA (indicated by a 28-joint disease activity score ESR >3.2) despite treatment with methotrexate (MTX) 12mg per week were included in this open label prospective study and started on TCZ (8 mg/kg every 4 weeks). All patients used a stable dosage of MTX, and were not allowed to use steroids or bisphosphonates during the study period. The BMD of the lumbar spine and femoral neck was measured by dual-energy X-ray absorptiometry at baseline and 52 weeks after initiating TCZ. Results: Seventy-eight patients completed this study. The BMD of the lumbar spine and femoral neck remained stable after 1 year of TCZ treatment. In 33 patients who had osteopenia at baseline, there was a significant increase in the BMD of the lumbar spine (0.022±0.042; P<0.05) and femoral neck (0.024±0.0245; P<0.05). Conclusions: TCZ affects the BMD in patients who had active RA despite treatment with MTX. The BMD of the lumbar spine and femoral neck in patients with normal BMD at baseline was stable. TCZ increased the BMD of patients who had osteopenia at baseline. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1088